Seven Fundamental Movements and Circuit Program Design - Sands, W. A.; McNeal, J. R.; Jemni, M. (coachesinfo.com)
Circuit training is an integral part of gymnastics conditioning at virtually all levels. The primary advantage of circuit training is time-efficiency. Well-designed and supervised conditioning circuits can achieve a large amount of physical work in a relatively small amount of time. Thus, circuit training has been a favorite conditioning tool of gymnastics coaches for many years (Sands, 1984; Sands & McNeal, 1997). Designing a conditioning circuit for gymnastics requires careful planning and some fundamental knowledge of the effects of training. Gymnastics conditioning circuits must be designed to meet the specific conditioning objectives. One of the most important principles of conditioning is - specificity. The principle of specificity means that conditioning should involve similar movements as those commonly found in gymnastics skills. Specificity is sometimes "over-interpreted" to mean that the athlete should perform conditioning exercises exactly the same as seen in the actual movements, usually with added resistance. Of course, the only way to do a movement exactly the same is to do the movement itself. Adding resistance to sport movements may be appropriate at some times, but adding resistance to a skilled movement is usually not a good idea (Siff, 2000). For example, wearing ankle weights while tumbling may inhibit the normal neuromuscular stimulation pattern and thus harm rather than aid tumbling performance. Weights added to the ends of limbs changes the mass distribution of the athlete considerably, and thereby changes the movement pattern. Coaches should proceed very carefully when adding weight to a skilled movement in order to achieve skill-specificity. In addition to movement similarity, it is very important that the conditioning exercises give the body an unambiguous message of how you want the body to change or adapt. For example, if you want the body to be able to run 26 miles, it is important that the training stimuli be similar to running for more than two hours. Performing handstand push-ups will probably not help a marathon runner (wrong muscles, wrong skill). Performing 50 meter sprints will probably not be of much benefit (wrong energy system, wrong pace). And, although 50 meter sprints will make you tired, the fatigue is of a different type than that experienced in long distance running. Rowing exercises may enhance endurance, but marathon runners don't row during their race (wrong skill). Specificity penetrates skilled movement even more. Conditioning for particular gymnastics movements is specific to the range of motion of the limbs, the speed of the movement, the type of movement, the duration of movement, the tension type and so forth. This further amplifies the importance of movement similarity between conditioning and performance movements (Siff, 2000). Developing a Circuit Training Program Circuit training has been used in athletic training for some time (Scholich, 1992). Circuit training involves conditioning activities with systematic movement of an athlete or groups of athletes from one conditioning "station" or exercise to another in a predetermined format. Circuit stations can enforce a certain number of repetitions, and thus time indirectly. Circuit stations can also enforce a certain amount of time for each station via a stopwatch or predetermined signal, thus ensuring a certain time per station directly. By manipulating the number and type of exercises, order of exercises, duration of work periods, duration of rest periods, and number of times through the entire circuit, the coach and athlete can exert enormous control over the nature of the training stimuli that are achieved and thus achieve control over training specificity.